Research on the Construction of Financial Shared Service Centers for Group Companies - Sun, Jiangyan; Yi, Fengyun (International Journal of Global Economics and Management, 2024)
With the rapid development of economic globalization and information technology, the number of global enterprises is growing rapidly, and the scale of enterprises is also constantly expanding. More and more enterprises are expanding their business overseas. The increasing complexity of business management is caused by the increase in business. The models of traditional financial management can no longer meet the development needs of modern enterprises. In order to strengthen internal control and improve market competitiveness, enterprises have begun to apply the financial shared service center model to solve problems in the development process. This article introduces the meaning, role, goals, and differences of financial shared service centers, and explores how to build a financial shared service center model. Finally, a summary is provided.